A R2R3-MYB Transcription Factor Gene, BpMYB123, Regulates BpLEA14 to Improve Drought Tolerance in Betula platyphylla - Lv, Kaiwen; Wei, Hairong; Liu, Guifeng (Frontiers in Plant Science, 2021)
Drought stress causes various negative impacts on plant growth and crop production. R2R3-MYB transcription factors (TFs) play crucial roles in the response to abiotic stress. However, their functions in Betula platyphylla haven't been fully investigated. In this study, a R2R3 MYB transcription factor gene, BpMYB123, was identified from Betula platyphylla and reveals its significant role in drought stress. Overexpression of BpMYB123 enhances tolerance to drought stress in contrast to repression of BpMYB123 by RNA interference (RNAi) in transgenic experiment. The overexpression lines increased peroxidase (POD) and superoxide dismatase (SOD) activities, while decreased hydrogen peroxide (H2O2), superoxide radicals (O2-), electrolyte leakage (EL) and malondialdehyde (MDA) contents. Our study showed that overexpression of BpMYB123 increased BpLEA14 gene expression up to 20-fold due to BpMYB123 directly binding to the MYB1AT element of BpLEA14 promoter. These results indicate that BpMYB123 acts as a regulator via regulating BpLEA14 to improve drought tolerance in birch.